Pseudoscalar mesons with symmetric bound state vertex functions on the light front - Yabusaki, George H. S.; Ahmed, Ishtiaq; Paracha, M. Ali; Melo, J. P. B. C. de; El-Bennich, Bruno [UNESP] (Amer Physical Soc, 2015)
We study the electromagnetic form factors, decay constants and charge radii of the pion and kaon within the framework of light-front field theory formalism where we use an ansatz for the quark-meson interaction bound-state function which is symmetric under exchange of quark and antiquark momentum. The above-mentioned observables are evaluated for the + component of the electromagnetic current, J(+), in the Breit frame. We also check the invariance of these observables in other frames, whereby both the valance and the nonvalence contributions have to be taken into account, and study the sensitivity of the electromagnetic form factors and charge radius to the model's parameters; namely, the quark masses, m(u) = m((d) over bar), m((s) over bar), and the regulator mass, m(R). It is found that after a fine-tuning of the regulator mass, i.e. m(R) = 0.6 GeV, the model is suitable to fit the available experimental data within the theoretical uncertainties of both the pion and kaon.